THE EFFECT OF CONTENT-BASED INSTRUCTION TOWARDS STUDENTS’ READING COMPREHENSION ON POST PANDEMIC PERIOD AT SMKN 2 MATARAM - Sabrina Damayanti; I Made Permadi Utama; Sudirman (Sinar Lima, 2024)
There were three main problems faced by students at SMKN 2 Mataram after the pandemic period. First is limited interaction between teacher and students during the pandemic period meant that students did not receive clear instructions for reading, practicing, or presenting the required material. This research was aimed to find out the effect of Content-Based Instruction towards students’ reading comprehension on post pandemic period at SMKN 2 Mataram. This research was experimental research with non-equivalent control group design. The sample of this research were students of XI ULW 1 as experimental class, and students of XI ULW 2 as control class. Experimental class was treated by using Content-Based Instruction, and control class was treated by using Task Based Learning as conventional way of teaching. The instrument used a lesson plan and reading test that consist of 25 items in the form of multiple choices. The research data was collected from the pre-test and post-test results of both groups and analyzed using independent sample t-test. According to the results, it showed that the score of sig. (2-tailed) = 0.04 which is smaller than the significance level 0.05 which means there was significant difference between the scores of experimental and control groups. It can be concluded that Content-Based Instruction had an effect on students’ reading comprehension on post pandemic period at SMKN 2 Mataram. The effect of CBI that were able to form active and independent students made CBI worth considering for use in the teaching and learning process.